Non-native and native teachers' perceptions on team-teaching approach: case of the JET programme - Hasegawa, Hiroshi (University of Tasmania, 2008)
Since the mid-1990s, research on non-native speaker teachers (NNSTs) in foreign language has been received with increasing interest (Illurda, 2005) and various discussions about its scope have been explored. The discussions include the perceptions of NNSTs and native speaker teachers (NSTs) in terms of their performance and the impact of the team-teaching approach. There has been a need for further investigations in the use of team-teaching in Japan, which was instigated during the Japan Exchange Teaching (JET) programme. The aim of this paper is to present multiple implications based on an analysis of the opinions of Japanese Teachers of English (JTEs) and Assistant Language Teachers (ALTs) who are involved in the JET programme. In order to do so, this paper demonstrates that 10 JTEs and 12 ALTs experience vexations and that these compromise the potential of the EFL team teaching in Japan. Special concentration on the mutual perspectives of JTEs as NNSTs as well as those of ALTs as NSTs makes this study more uniquely constituted and different from others which have been concerned more with the perspectives of either one or the other group.